The Merger Turmoil of PT. Pesona Traditional and PT. Tech-stay: Cultural Integration Toward Smart Hospitality - Dede Ruslandi; Mahriani; Aulia Eka; Riva’atul Mahmudah; Muhammad Akmal Nadzar; Durahman (PT. Hanken Sukses Jaya, 2025)
The hospitality industry is facing increasing pressure from digital transformation,shifting customer expectations, and growing demands for operational efficiency. Inthis context, smart hospitality has emerged as a strategy that integrates digitaltechnologies with high-value service experiences. However, digital transformationwithin merger contexts often generates significant challenges related toorganizational culture and human resources. This study aims to analyze the post-merger crisis between PT. Pesona Tradisional and PT. Tech-Stay, which formed PT.Hospitality Global Indonesia (HGI), particularly focused on cultural integrationtoward smart hospitality. The study concludes that the success of smart-hospitalitymergers depends on human-centered, organizational development–based changemanagement. It recommends participative change strategies, strengthenedstakeholder management, and the gradual integration of high-touch and high-techvalues to support sustainable merger outcomes in service industries withindeveloping countries.